Pembuatan Shortening dari Minyak Wijen dan Minyak Sawit Merah Menggunakan Metode Blending - Nina Veronika (Politeknik Kampar, 2023)
Shortening is a plastic fat that can be used as a medium for making bread and fillers in confectionery products, shortening functions to improve taste, structure, texture and increase the volume of bakery products. Initially, shortening was made from animal fat, but now it is switching to using vegetable oil through a process of hydrogenation, interesterification and mixing of 2 or more oils/fats (blending). This study aims to determine the process of making shortening, by looking at the effect of the comparison WIJEN:RPO on the quality of shortening. Shortening is made using the blending method by mixing the oil phase with variations in the WIJEN:RPO ratio used are 100:0, 80:20, 60:40, 40:60, 20:80. Shortening with quality close to the best results from a variable rasio of 100:0. The quality of the shortening produces has a water content of 0,016, a free fatty acid content of 0,54%, for the organoleptic test itself includes color, taste and aroma, the respective percentage are : color 100%, taste 0%, and aroma 28%.